Cumulative incidence of admission to permanent residential aged care for Australian women - A competing risk analysis - Peta Forder; Julie Byles; Kha Vo; Cassie Curryer; Deborah Loxton (Elsevier, 2018)
Abstract Objective: To provide a direct estimate of the risk of admission to permanent residential aged care among older women while accounting for death, according to housing type and other variables. Methods: A competing risk analysis from 8,867 Australian women born 1921-26, using linked data from the Australian Longitudinal Study on Women's Health (ALSWH), Residential Aged Care (RAC), and the Australian National Death Index. Results: After accounting for deaths, around 35% of women will be admitted to RAC between ages 73 and 90. The conditional cumulative incidence of admission to RAC was 26.9% if living in a house, compared to 36.0% from an apartment, 43.6% within a retirement village, and 37.1% if living in a mobile home. Each one‐year increase in age was associated with a relative 17% increased risk of RAC. Conclusions: Around one‐third of women will enter RAC between age 73 and 90. Living in a house had the lowest risk of entering residential aged care over time. Implications for public health: These findings have important implications for planning for aged care services, including the role of housing in delaying admission to residential aged care, and the need for residential care by a high proportion of women towards the end of life.